Fundamental approach on orthotic device for patients with osteoarthritis of knee considering screw home movement - Zhiqiang WU; Tomonori YAMAMOTO; Rafiuddin SYAM; Satoru SHIBATA (Journal of Biomechanical Science and Engineering, 2016)
In this study, as a fundamental approach to realize orthotic device for patients with osteoarthritis of the knee considering screw home movement, bending and extension movements of lower thigh of able-bodied persons are analyzed and inherent screw home movement is examined. The analyzed extension movement of lower thigh with screw home movement is mathematically modeled and the structure of an orthotic device is proposed based on the model. It is confirmed by the simulation based on FEM analysis that the force acting on the leg when using the proposed orthotic device is helpful to realize normal screw home movement and valgus rotation, which is expected to be useful for patients with osteoarthritis of the knee.